(untitled) (Minerva, 2019)
Some sources tell us that Aristotle prepared for Alexander a recensio of the Iliad. R. Pfeiffer has examined the problem; according to his opinion, Aristotle did not prepare a διόρθωσις, but merely a copy (έκδοσις). Based on a more accurate inquiry of the sources, this paper tries to prove that this so-called «Iliad of the casket» was really a recensio.